Landslide hazard zonation, mapping and investigation of triggering factors in Phewa lake watershed, Nepal - Basnet, P.; Balla, M. K.; Pradhan, B. M. (Banko Janakari, 2013)
The landslide triggering factors were investigated followed by the thematic maps and landslide distribution map prepared and classified using the GPS and GIS Softwares like CartaLinx, ArcView and ERDAS IMAGINE in Sarangkot and Kaskikot Village Development Committees, Kaski district. In analytical hierarchy process, the factors for zonation were compared by Couple Comparison Method and their weights were determined using Arithmetic Mean Method and earned weight values of each factor. The landslide hazard zonation model was employed to prepare landslide hazard zonation map of the study area, and then classified into five relative hazard classes using the equal interval classification method. Finally, the landslide hazard zonation map was crossed with the landslide distribution map and the model applicability was confirmed by determining the per hazard class percent of area covered by the landslide. In the land hazard zonation map, 0.44% of the study area was in very low hazard, 2.11% in low hazard, 54.92% in moderate hazard, 21.34% in high hazard and 21.19% in very high hazard area. The major portion of the study area was on the moderate zone whereas the least portion was on the very low hazard zone. In the study area, most of the high and very high hazard class areas were found occupying the areas closer to the linear triggering factors like presence of linement and fault, presence of motorable road and presence of rivers and streams. The landslide density of the study area was found to be 0.44 per km2 indicating the higher hazard susceptibility of the area. DOI: http://dx.doi.org/10.3126/banko.v22i2.9198 Banko Janakari: A Journal of Forestry Information for Nepal Vol. 22, No. 2, 2012 November Page: 43-52 Uploaded date: 12/1/2013